Analisis Progresivitas Kebijakan Publik Tentang Aparatur Sipil Negara - Syukron, Nurkholis; Irawan, Andri (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2026)
This study aims to analyze the progressiveness of the policies set forth in Law of the Republic of Indonesia Number 20 of 2023 on the Civil Service. The Civil Service is one of the state’s instruments tasked with serving the public in the conduct of state and government affairs. This study employs a descriptive method with a qualitative approach. Data was collected through an analysis of the law (statutory approach) as the primary legal source. The results of the research indicate that there are several articles in Law of the Republic of Indonesia Number 20 of 2023 on the Civil Service. Some articles contain legal provisions that are relatively central, while others are complementary in nature. Both types of changes in the regulations governing the civil service are, in essence, rational consequences of the enactment of a new legal instrument. The implications are clearly felt by the entire civil service, whether they hold the status of civil servants or those with the status of government employees under employment contracts. Thus, this research ideally can provide an important contribution to the understanding of public policies governing the civil service.